Indication and Usefulness of Bile Juice Cytology for Diagnosis of Gallbladder Cancer - Hiroshi Itsuki; Masahiro Serikawa; Tamito Sasaki; Yasutaka Ishii; Ken Tsushima; Yoshinari Furukawa; Yoshiaki Murakami; Koji Arihiro; Kazuaki Chayama (Gastroenterology Research and Practice)
Aim. We examined the effectiveness of bile juice cytology for distinguishing between benign and malignant gallbladder lesions of the protruding type with various sampling points, sampling methods, and macroscopic forms in order to discuss the effectiveness of the endoscopic transpapillary gallbladder drainage (ETGD) cytology. Methods. We studied 162 cases of patients with a lesion localized within the gallbladder. At first, we examined the effectiveness for diagnosis of ETBD cytology using ERC and then that of the first ETGD cytology after placing the ETGD. Next, we examined the diagnostic effectiveness of the washed ETGD cytology by using the ETGD. Finally, we examined complications. Results. In the final diagnoses, we identified 33 cases of adenocarcinoma, 10 cases of adenoma, 63 cases of ADM, 35 cases of nonneoplastic polyp, and 21 cases of chronic cholecystitis. It was found that the sensitivity of ETBD cytology was 3.6% and that of ETGD cytology was 59.1%. In the comparison of diagnostic effectiveness of cytologic diagnosis using samples of bile juice from the gallbladder collected by different methods, the sensitivities were 38.9% and 73.3% for the first and washed ETGD cytologies, respectively. In the comparison of the diagnostic effectiveness of gallbladder bile juice cytology using samples collected for different forms of lesion and by different methods, the sensitivities were 38.9% and 73.3%, respectively, for the first and washed ETGD cytologies for flat gallbladder wall thickening, while it was impossible to diagnose for lesions of GB polyp. Conclusion. For diagnosis of gallbladder cancer, we consider that the ETGD cytology should be taken into consideration for lesions of flat gallbladder wall thickening, for which it is difficult to distinguish between benign and malignant lesions.